Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).